Epidemiology of grain mould of sorghum in South Africa and Ethiopia - Terefe, Tarekegn Geleta (University of the Free State, 2002)
A study aimed to determine grain mould fungi associated with sorghum cultivars grown In two localities (Cedara and North West/Free State) in South Africa indicated Fusarium subglutinans and F. graminearum to be the predominant species. Fusarium proliferatum followed by F. thapsinum was however more commonly isolated from Ethiopian cultivars. Bipolaris sorghicola and Phoma sorghina were found in some cultivars from both countries. C.urvularia clavata was frequently isolated from South African sorghum cultivars. C. lunata was encountered occasionally although its prevalence was relatively high in Ethiopian cultivars. Alternaria alternata had the highest incidence in cultivars from both countries. Colletotrichum graminicola (Cl. Graminicola) occurred only in grains from Cedara. F. proliferatum and C. clavata were isolated from the embryos of many cultivars. F. graminearum, A. alternata, P. sorghina and Cl. graminicola were occasionally found in embryos of sorghum grains. Pathogenicity studies showed that F. subglutinans, Cl. graminicola and B. sorghicola were important in causing various kinds of grain damage (seed discolouration, 1000 grain mass and seed germination). Grain damage tends to increase when many species occurred together rather than separately. Most Fusarium spp., B. sorghicola and C. clavata had relatively higher transmission rates to seedlings and significantly reduced seedling vigour. Pathogens with embryo invading capacity had generally higher rates of transmission. During a three-year period (1999/2000 to 200112002), the relationship between weather variables and grain mould development was assessed in field trials at Cedara, South Africa. Significant positive correlations were observed between the incidence of A. alternata, Curvularia spp. (C. lunata and C. clavata), Fusarium spp. (F. proliferatum and F. graminearum), B. sorghicola and minimum temperature, total and frequency of rainfall (average during 4-6 or 5-8 weeks after flowering based on hybrid sorghum used). However, significant correlations could not be established between seed damage parameters such as seed germination and 1000-grain mass and incidence of different grain mould fungi. Linear models that described relationships between disease incidence and minimum temperature and between disease incidence and rainfall frequency were developed. Models that used minimum temperature as predictor explained 60 to 82% of variation in disease incidence. Frequency of rainfall explained 93% of the variation in disease incidence in one cultivar. The most susceptible grain development stage of major Ethiopian sorghum cultivars was determined in field trials. Higher infection incidences and damage to grains were associated mainly with dough stage of grain development. Significantly higher incidence of major mould fungi (Fusarium proliferatum, F. thapsinum and F. graminearum and B. sorghicola) consistently occurred during milk to dough stages. Incidences of C. lunata and P. sorghina were generally lower at all stages. Infection by P. sorghina increased at anthesis. Frequency of Alternaria spp. and Epicoccum spp. increased significantly after the dough growth stage. Grain colonisation by Cladosporium spp. was not affected significantly by growth stage. Differences in the incidence of fungi over growth stages were more evident in susceptible than resistant cultivars. The incidence of Fusarium spp. and B. sorghicola was negatively correlated with percentage germination but positively correlated with grain discolouration. A negative correlation was found between the incidence of B. sorghicola and 1000-grain mass. In the greenhouse, artificial inoculation at the soft dough growth stage with C. lunata, Fusarium moniliforme and P. sorghina, resulted in a greater reduction in seed germination than inoculation at anthesis. Sorghum cultivars from South Africa and Ethiopia were evaluated for resistance to grain mould and characterized for physical and chemical characteristics of grains. The objective was to determine resistance factors associated with grains. Resistant cultivars contained significantly greater amounts of phenols including glume proanthocyanidins, seed flavan-4-ols, apigeninidins and/or luteolinidins compared with susceptible cultivars. A highly significant negative correlation was observed between ergosterol content of grains and level of glume proanthocyanidins suggesting the role of glume proanthocyanidins in mould resistance. Cultivars containing diverse and increased concentrations of phenolic compounds had moderate to high resistance levels. Most of the resistant cultivars have coloured seed pericarps and glumes. Resistance was found in early, medium as well as late maturing cultivars. The present study revealed the widespread occurrence of grain mould pathogens among cultivars commonly grown in Ethiopia and South Africa. Hence, susceptible cultivars maturing during moist and warm conditions may suffer significant grain yield and quality losses. This dissertation provides important information mainly about the influence of meteorological factors and plant host growth stage on grain mould dynamics. It is hoped that these findings may motivate future studies particularly on the epidemiology of grain mould, to which little attention has been paid.

'n Ondersoek is gedoen om swamspesies te identifiseer wat graanskimmel by sorghumkultivars veroorsaak. Fusarium subglutinans en F. graminearum was oorheersende vanuit die twee lokaliteite in Suid-Afrika (Cedara en Bethlehem) geisoleer. Fusarium proliferatum gevolg deur F. thapsinum was egter meer algemeen vanaf Ethiopiëse kultivars geïsoleer. Curvularia clavata was gereeld vanaf Suid-Afrikaanse kultivars geïsoleer terwyl C lunata net soms opgemerk is, maar laasgenoemde was baie meer opvallend by Ethiopiëse kultivars. Alternaria alternata het die hoogste voorkoms op kultivars uit beide lande getoon. Colletotrichum graminicola (C graminicola) het net op graan vanaf Cedara voorgekom. F. proliferatum en C clavata was vanuit die embrios van meeste kultivars geïsoleer. F. graminearum, A. alternata, P. sorghina en C graminicola het egter net sporadies in embrios voorgekom. Patogenisiteitstoetse het getoon dat F. subglutinans, C. graminicola, en B. sorghicola verskeie tipes graanskade (saadverkleuring, 1000-graan massa en saadontkieming) veroorsaak. Graanskade neig om toe te neem wanneer spesies gesamentlik optree eerder as afsonderlik. Meeste Fusarium spp., B. sorghicola en C clavata kan teen hoë frekwensie na saailinge oorgedra word en ook kiemkragtigheid van saailinge beduidend verlaag. Die verwantskap tussen weerveranderlikes en graanskimmel was oor 3- seisoene (1999/200 tot 2001/2002) by Cedara gekwantifiseer. Beduidende positiewe korrelasies is waargeneem tussen die voorkoms van A. alternata, Curvularia spp. (C lunata en C clavatai, Fusarium spp. (F. proliferatum en F. graminearum) B. sorghicola en minimum temperatuur, totale reënval asook die frekwensie van reën (gemiddeld tussen 4-6 of 5-8 weke na blomtyd nagelang groeiperiode van sorghumvariteite). Beduidende korrelasies kon nie tussen saadeienskappe soos ontkieming, 1000-graan massa en voorkoms van verskillende graanskimmelswamme vasgestel word nie. Lineêre modelle is ontwikkel wat die verwantskap tussen siektevoorkoms en minimum temperatuur asook reën frekwensie beskryf. Modelle wat minimum temperatuur as voorspeller gebruik het, kon tussen 60 en 80% van die variasie in siektevoorkoms verduidelik. Frekewensie van reën het 93% van die variasie in siektevoorkoms in een spesifieke kultivar beskryf. Die mees vatbare graan-onwikkelingstadium van vername Ethiopiëse kultivars was in veldproewe vasgestel. n Hoër voorkoms van infeksie en skade by graan was hoofsaaklik waargeneem by deegstadium van graanontwikkeling. Beduidende hoër voorkoms van die vernaamste swamme (F. proliferatum, F. thapsinum en F. graminearum en B. sorghicola) het gereeld tussen melk- en deegstadiums voorgekom. Die voorkoms van C. lunata en P. sorghina was oor die algemeen laer by alle groeistadiums. Infeksie deur P. sorghina het by stuifmeelstort toegeneem. Die frekwensie van Alternaria spp. en Epicoccum spp. het noemenswaardig na afloop van deegstadium toegeneem. Kolonisasie van graan deur Cladosporium spp. was nie beduidend deur groeistadiums beïnvloed me. Die invloed van groeistadiums was minder opvallend in weerstandbiedende kultivars. Die voorkoms van Fusarium spp. en B. sorghicola was negatief gekorreleerd met ontkieming, maar postief met verkleuring van graan. 'n Negatiewe korrelasie was tussen die voorkoms van B. sorghicola en lOOO-graan massa waargeneem. Onder kunsmatige toestande in die glashuis, het inokulasie met C. lunata, F. moniliforme en P. sorghina 'n groter afname in saadontkieming by sagtedeegstadium meegebring as by stuifmeelstort Sorghumkultivars van Suid-Afrika en Ethiopië was geëvalueer ten opsigte van fisiese- en chemise-weerstandsmeganismes teen graanskimmel. Saad van weerstandbiedende kultivars het groter hoeveelhede fenole, proantosianidiene, flavan-4-ole, apigenidiene en/of luteolinidiene bevat in vergelyking met vatbare kultivars. 'n Hoogs beduidende negatiewe korrelasie was tussen ergosterolinhoud van sade en vlakke van proantosianidiene in saadkaffies waargeneem, wat die moontlike rol van proantosianidiene in weerstand teen graanskirnmel aandui Verskeie fenoliese verbindings het ook bygedra tot weerstandsvlakke. Weerstand is in alle groeiseisonlengte kultivars waargeneem. Die huidige studie het getoon dat graanskimmelpatogene by sorghum in Suid-Afrika en Ethiopië wyd verspreid voorkom. Vatbare kultivars wat tydens vogtige en warm toestande ryp word, kan verliese in opbrengs en kwalitiet ly. Hierdie proefskrif bevat belangrike inligting met betrekking tot die invloed van meteorologiese faktore en plant groeistadiums op die dinamika van graanskimmel. Dit sal hopelik verdere studies stimuleer, veralop die epidemiologie van graanskimmel wat tot dusver min aandag geniet het.
Thesis (Ph.D. (Plant Sciences (Plant Pathology))--University of the Free State, 2002
Keywords: Sorghum -- Diseases and pests -- South Africa; Sorghum -- Diseases and pests -- Ethopia